What strategies do desk-based workers choose to reduce sitting time and how well do they work? Findings from a cluster randomised controlled trial 11 Medical and Health Sciences 1117 Public Health and Health Services - Stephens, S.; Eakin, E.; Clark, B.; Winkler, E.; Owen, N.; Lamontagne, A.; Moodie, M.; Lawler, S.; Dunstan, D.; Healy, Genevieve (Biomed Central, 2018)
© 2018 The Author(s). Background: Large amounts of sitting at work have been identified as an emerging occupational health risk, and findings from intervention trials have been reported. However, few such reports have examined participant-selected strategies and their relationships with behaviour change. Methods: The Stand Up Victoria cluster-randomised controlled trial was a workplace-delivered intervention comprising organisational, environmental and individual level behaviour change strategies aimed at reducing sitting time in desk-based workers. Sit-stand workstations were provided, and participants (n = 134; intervention group only) were guided by health coaches to identify strategies for the 'Stand Up', 'Sit Less', and 'Move More' intervention targets, including how long they would stand using the workstation. Three-month workplace sitting and activity changes (activPAL3-assessed total sitting, prolonged sitting (i.e., sitting =30 min continuously) and purposeful walking) were evaluated in relation to the number (regression analysis) and types of strategies (decision-tree analysis). Results: Over 80 different strategies were nominated by participants. Each additional strategy nominated for the 'Stand Up' intervention target (i.e. number of strategies) was associated with a reduction in prolonged sitting of 27.6 min/8-h workday (95% CI: -53.1, - 2.1, p = 0.034). Types of strategies were categorised into 13 distinct categories. Strategies that were task-based and phone-based were common across all three targets. The decision tree models did not select any specific strategy category as predicting changes in prolonged sitting ('Stand Up'), however four strategy categories were identified as important for total sitting time ('Sit Less') and three strategy categories for purposeful walking ('Moving More'). The uppermost nodes (foremost predictors) were nominating > 3 h/day of workstation standing (reducing total workplace sitting) and choosing a 'Move More' task-based strategy (purposeful walking). Conclusions: Workers chose a wide range of strategies, with both strategy choice and strategy quantity appearing relevant to behavioural improvement. Findings support a tailored and pragmatic approach to encourage a change in sitting and activity in the workplace. Evaluating participant-selected strategies in the context of a successful intervention serves to highlight options that may prove feasible and effective in other desk-based workplace environments. Trial registration: This trial was prospectively registered with the Australian New Zealand Clinical Trials register (ACTRN12611000742976) on 15 July 2011,